KAJIAN INTRUSI AIR LAUT BERDASARKAN ANALISA GEOLISTRIK DI DESA SENTANG, KABUPATEN SERDANG BEDAGAI, SUMATERA UTARA - Annisa Intan Yustisia Rahmalina; Riam Marlina Amsya; Ahmad Fadhly; Ferdinan Pandiangan (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
This research was carried out in Sentang Village, Teluk Mengkudu District, Serdang Bedagai Regency, North Sumatra Province. The purpose of this activity is to determine the distribution of sea water intrusion at the research site. This information is very useful for knowing the extent to which the location area has been intruded by seawater. The method used is the 1D resistivity method with the Schlumberger configuration, with 3 measurement paths. The distance between the measurement paths is close together, where the total length of the stretch of each of the two measuring points is Track I of 350 meters, Track II is 200 meters and Track III is 350 meters. Based on the measurement data and data processing, it is suspected that the research location is in an alluvium formation, where the lithology is gravel, sand and clay. The results of the resistivity measurements obtained by the three tracks are seawater intrusion, namely: The first track is at a depth of 2.68 - 10.8 m with a resistivity value of 4.06 m, the second track is at a depth of 2.34 - 9.32 m with a resistivity value of 4.94 m The third track is at a depth of 2.56 - 9.8 m with a resistivity value of 4.5 m. Meanwhile, residents' well water testing activities were used as supporting data which was correlated with resistivity data. It was concluded that the research area had been intruded by seawater at a depth of 2.34 – 10.8 meters and at a depth of 80.1 - 125 meters it was suspected that it had not been contaminated with seawater. If you want to get fresh water wells that have not been contaminated, you can drill with a depth of 80.1 to 125 meters in a location that has been studied to get drinking water fit for consumption.